Access to Justice Based on Expert Testimony in Tax Crimes: An Integrated Criminal Justice System Perspective in Indonesia - Setia Untung Arimuladi (Universitas Negeri Semarang, 2022)
Several cases of criminal acts in the field of taxation show differences in calculating losses in state revenue between prosecution and judge's decisions; several decisions acquit or punish a defendant. There is still ambiguity in treatment between the application of criminal tax sanctions or administrative tax sanctions, so it is necessary to and urges to conduct a study of access to justice in terms of setting expert statements in tax crimes based on the principle of equality before the law and the principle of checks and balances in building a solid integrated criminal justice system. Two main conclusions were drawn based on case studies and literature reviews using the normative juridical method, the access to justice, and the progressive legal models. First, experts in calculating losses on state income and experts on tax regulations in taxation are still dominated by internal employees of the Directorate General of Taxes (DGT), which of course will reduce the value of the independence of the experts' statements because they cannot be separated from conflicts of interest with their institutions. Second, experts who provide information in a tax crime must be competent, independent, capable, and objective in providing information and opinions so that it needs to be made in the form of a cross-institutional ad hoc team with accountability in the form of a report on the results of the examination. It is necessary and urgent to provide legal certainty in access to justice for expert testimony to update the rules regarding procedures for expert testimony in tax crimes.